Quantitative biomechanical optimization of neochordal implantation location on mitral leaflets during valve repairCentral MessagePerspective - Pearly K. Pandya, BS; Robert J. Wilkerson, BS; Annabel M. Imbrie-Moore, PhD; Yuanjia Zhu, MD, MS; Mateo Marin-Cuartas, MD; Matthew H. Park, MS; Y. Joseph Woo, MD (JTCVS Techniques)
Objective: Suture pull-out remains a significant mechanism of long-term neochordal repair failure, as demonstrated by clinical reports on recurrent mitral valve regurgitation and need for reoperation. The objective of this study was to provide a quantitative comparison of suture pull-out forces for various neochordal implantation locations. Methods: Posterior leaflets were excised from fresh porcine mitral valves (n = 54) and fixed between two 3-dimensional–printed plates. Gore-Tex CV-5 sutures (WL Gore & Associates Inc) were placed with distances from the leading edge and widths between anchoring sutures with values of 2 mm, 6 mm, and 10 mm for a total of 9 groups (n = 6 per group). Mechanical testing was performed using a tensile testing machine to evaluate pull-out force of the suture through the mitral valve leaflet. Results: Increasing the suture anchoring width improved failure strength significantly across all leading-edge distances (P < .001). Additionally, increasing the leading-edge distance from 2 mm to 6 mm increased suture pull-out forces significantly across all suture widths (P < .001). For 6-mm and 10-mm widths, increasing the leading-edge distance from 6 mm to 10 mm increased suture pull-out forces by an average of 3.58 ± 0.15 N; in comparison, for leading-edge distances of 6 mm and 10 mm, increasing the suture anchoring width from 6 mm to 10 mm improves the force by an average of 7.09 ± 0.44 N. Conclusions: Increasing suture anchoring width and leading-edge distance improves the suture pull-out force through the mitral leaflet, which may optimize postrepair durability. The results suggest a comparative advantage to increasing suture anchoring width compared with leading-edge distance.